Editorial : Student Affairs in Complex Contexts (Journal of Student Affairs in Africa, 2021)
While the Western world – with Brexit, Trump, Festung Europa, and so forth – seems to be increasingly retreating into narrow nationalism, the Journal of Student Affairs in Africa is connecting African academics, executives and administrators and is becoming an evermore accessed international, African platform for publishing research on higher education and Student Affairs in Africa. In this issue, we do not only publish several commentaries on the recent Global Summit of Student Affairs and Services held in October 2016 at Stellenbosch University, South Africa. We also publish contributions from Ethiopia alongside articles from Australia, the USA, and universities in South Africa (University of the Free State, University of Johannesburg). Moreover, the first 2017 issue will be guest edited by colleagues from the International Association of Student Affairs and Services (IASAS),which will look beyond the African continent with contributions from Australia, Canada,China, Europe and America. Dissatisfaction and frustration with political leaders have sent students pouring out intothe streets, demanding free education in South Africa, demanding an increase on higher education funding in Ireland and protesting the presidential election outcome in the US. In the Democratic Republic of Congo, the Minister of Higher Education has ordered a freeze on fee increments following student protests, while in Niger student protests have pushed the government to agree to provide additional funding for higher education. On the African continent, there are various challenges facing Student Affairs professionals, for example, providing support to students whose payments by the Tanzania’s HigherEducation Student Loan Board (HESLB) have been delayed due to administrative problems in providing correct student data and student results. In Egypt, there is need to support students returning to institutional residential life at the Al Azhar Seminary where the facility was closed for two years. There is need to support Student Affairs colleagues, academics and students in Nigeria where unpaid salary increments threaten the educational project.
Keywords: Western world; Brexit; Trump; Festung Europa; Journal of Student Affairs in Africa; African; Global Summit of Student Affairs and Services; International Association of Student Affairs and Services (IASAS); Australia; Canada; South Africa; China; America; Democratic Republic of Congo; Tanzania; Egypt; Nigeria